Scavenging of hydroxyl radicals generated in human plasma following X-ray irradiation - Hosokawa, Y.; Sano, T. (Radiation protection dosimetry, 2015)
There are various antioxidant materials that scavenge free radicals in human plasma. It is possible that the radical-scavenging function causes a radiation protective effect in humans. This study estimated the hydroxyl (OH) radical-scavenging activity induced by X-ray irradiation in human plasma. The test subjects included 111 volunteers (75 males and 36 females) ranging from 22 to 35 years old (average, 24.0). OH radicals generated in irradiated human plasma were measured by electron spin resonance (ESR). The relationships between the amount of the OH radical and chemical and biological parameters [total protein, total cholesterol, triglycerides and hepatitis B surface (HBs) antibodies] were estimated in the plasma of the 111 volunteers by a multivariate analysis. The presence of HBs antibodies had the greatest influence on OH radical-scavenging activity. One volunteer who did not have the HBs antibody was given an inoculation of the hepatitis B vaccine. There was a remarkable decrease in the amount of OH radical generated from plasma after the HBs antibody was produced. The results indicate that the HBs antibody is an important factor for the scavenging of OH radicals initiated by X-ray irradiation in the human body.